Essential Spectrum and Fredholm Index for Certain Composition Operators - Yakes, Christopher J. (MATHEMATICA SCANDINAVICA, 2016)
We investigate a composition operator on H^∞(U), U a subdomain of the open unit disk, for which the essential resolvent has infinitely many components, and for which the Fredholm index of the resolvent operator attains all nonnegative integer values.